Tradition versus Innovation: A Comparison of NARA and ANRI’s Archival Management in the Digital Age - Oktaviana, Shanti Yesi Belina (Perpustakaan dan Arsip Universitas Gadjah Mada, 2025)
The United States (U.S.) leads at the forefront of modern archival innovation, while Indonesia advances digital transformation amidst the persistent influence of traditional approaches and conservative perspectives in conventional records management. The National Archives and Records Administration (NARA) in the U.S. and the National Archives of the Republic of Indonesia (ANRI) play key roles. A balanced approach combining tradition and innovation is essential for navigating transitional challenges. This study aims to provide a comparative analysis of archival management practices between The United States’s NARA and Indonesia’s ANRI, examining the interplay of traditional approaches and digital innovation. Using a descriptive qualitative methodology and literature review, the research highlights NARA’s advanced digital archival system and ANRI’s developmental stage, where cultural, policy and infrastructure challenges persist. The findings underline the importance of integrating traditional principles with innovative solutions for sustainable archive management. As both nations navigate the complexities of technological advancement, they prioritize data security and privacy measures.